Pelaksanaan Tugas Komisi Pemilihan Umum Daerah Dalam Sosialisasi Undang – Undang Nomor 7 Tahun 2017 Menjelang Pemilukada Dimasa Pandemi Covid-19 - Eylesia Elkel; Hendrik Salmon; Sherlock Halmes Lekipiouw (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The legal issues in this writing include (1) Is the Covid-19 Pandemic Affecting the Simultaneous Regional Head Elections and (2) How is the KPUD Implementation in Disseminating Law Number 7 of 2017 Ahead of the Regional Head Election during the Covid-19 Pandemic.Purposes of the Research: This writing aims to find out and analyze how the KPUD's duties are in socializing Law Number 7 of 2017 during the Covid-19 Pandemic. Methods of the Research: The research method used is normative, that is, research that primarily examines positive legal provisions and legal principles, explains and predicts the direction of future legal developments. This is because this research is a legal research, because the science of law has a special character (it is a sui generis discipline).Results of the Research: The results of the discussion of the writer of this thesis showed that the implementation of the Democratic Party was disrupted by the corona virus outbreak, one of which was the simultaneous Regional Head Election. Even the implementation of KPUD's Duties of Law Number 7 of 2017 concerning socialization ahead of the Regional Head General Election is disrupted, but the KPUD can cooperate with print or electronic media in order to make it easier for the public to know the procedures for conducting the Regional Head Election so that the KPUD's task in conducting socialization ahead of the Regional Head General Election can be carried out.